A review of two decades (1986 2008) of geochronological work in Heimefrontfjella, and geotectonic interpretation of western Dronning Maud Land, East Antarctica - Jacobs, Joachim (Polarforschung, 2009)
During two decades (1986 - 2008) of geochronological work in Heimefrontfjella, nearly 130 geochronological ages were produced using a wide range of geochronological techniques. The ages fall into four broad age groups from Archaean to Cenozoic times, revealing a long and complex geological history. In general, Heimefrontfjella consists of Mesoproterozoic high grade basement related to the ∼1100 Ma Maud Belt. This basement is overlain by Permo-Carboniferous sedimentary rocks and Jurassic lavas. Archaean and Palaeoproterozoic detrital zircon ages are recorded from meta-sedimentary rocks probably characterizing the foreland of the Maud Belt. The protolith and metamorphic ages of the Mesoproterozoic Maud Belt fall into two groups. An older age group from ∼1200-1100 Ma is related to back-arc and island arc volcanism. High-grade metamorphism in the Maud Belt is dated between 1090-1060 Ma and is thought to reflect continent-continent collision, possibly related to the formation of Rodinia. Regional cooling to below 500-300 °C at ∼1010-960 Ma in part of the mountain range might indicate rifting of Rodinia. The eastern part of the mountain range is overprinted by the ∼600-500 Ma East African-Antarctic Orogen. The orogenic front of this major mobile belt is exposed in the study area as the Heimefront Shear Zone. East of this major lineament all Ar-Ar, K-Ar and Rb-Sr mineral ages are reset to ∼500 Ma. Initial Gondwana rifting affected the area at c. 180 Ma, when the Bouvet/Karroo mantle plume caused dynamic uplift of the area, followed by burial underneath up to 2 km of Jurassic lava. This led to tempering of the basement up to about 100 °C, as indicated by apatite fission track data. The lava pile underwent erosion in Cretaceous time, when renewed rifting affected the region. Latest tectonic movements might be related to Cenozoic ice loading related to the built up of the Antarctic ice sheet.
Keywords: Dronning Maud Land; ekspedisjoner; geokronologi; geologi; tektonikk

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Pan-African granitoid magmatism in Central Dronning Maud land caused by delamination? - Kleinhanns, Ilka; Jacobs, Joachim; Roland, N W ([Geological Society of America], 2009)
Keywords: Dronning Maud Land; geologi

Proterozoic–Cambrian history of Dronning Maud Land in the context of Gondwana assembly - Bauer, Wilfried; Thomas, Robert J; Jacobs, Joachim (Proterozoic East Gondwana: Supercontinent Assembly and Breakup, 2003)
Dronning Maud Land contains a fragment of an Archaean craton covered by sedimentary and magmatic rocks of Mesoproterozoic age, surrounded by a Late Mesoproterozoic metamorphic belt. Tectonothermal events at the end of the Mesoproterozoic and in Late Neoproterozoic–Cambrian times (Pan-African) have been proved within the metamorphic belt. In western Dronning Maud Land a juvenile Mesoproterozoic basement was accreted to the craton at c. 1.1 Ga. Mesoproterozoic rocks were also detected by zircon SHRIMP dating of gneisses in central Dronning Maud Land, followed by a long hiatus for which geochronological data are lacking, an amphibolite to granulite facies metamorphism and syntectonic granitoid emplacement of Pan-African age have been dated. During this orogeny older structures were completely overprinted in a sinistral tranpressive deformation regime, leading to the mainly coast-parallel tectonic structures of the East Antarctic Orogen. Putting Antarctica back in its Gondwana position, the East Antarctic Orogen continues northward in East Africa as the East African Orogen, whereas a connection to the marginal Ross Orogen at the Pacific margin of East Antarctica is suggested along the Shackleton Range. The East Antarctic-East African Orogen resulted from closure of the Mozambique Ocean and collision of West and East Gondwana, i.e. western Dronning Maud Land was part of West Gondwana. During this collision the lithospheric mantle probably delaminated, allowing the asthenosphere to underplate the continental crust and producing heat for the voluminous, typically anhydrous, Pan-African granitoids of central Dronning Maud Land.
Keywords: Dronning Maud Land; geologi

Early Palaeozoic orogenic collapse and voluminous late-tectonic magmatism in Dronning Maud Land and Mozambique: insights into the partially delaminated orogenic root of the East African–Antarctic Orogen? - Jacobs, Joachim; Bingen, Bernard; Thomas, Robert J; Bauer, Wilfried; Wingate, Michael T D; Feitio, Paulino (Geological Society, London, Special Publications, 2008)
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; tektonikk

Pan-African granulites of central Dronning Maud Land and Mozambique: a comparison within the East-African-Antarctic orogen - Engvik, Ane K; Elvevold, Synnøve; Jacobs, Joachim; Tveten, E; de Azevedo, S; Njange, F (Antarctica - a keystone in a changing world: online proceedings for the 10th International Symposium on Antarctic Earth Sciences, 2007)
Granulite-facies metamorphism is extensively reported in Late Neoproterozoic/Early Palaeozoic time during formation of the East-African-Antarctic orogen (EAAO). Metamorphic data acquired from the Pan-African orogen of central Dronning Maud Land (cDML) are compared with data from northern Mozambique. The metamorphic rocks of cDML are characterised by Opx±Grt-bearing gneisses and Sil+Kfs-bearing metapelites which indicate medium-P granulite-facies metamorphism. Peak conditions, which are estimated to 800-900ºC at pressures up to 1.0 GPa, were followed by near-isothermal decompression during late Pan-African extension and exhumation. Granulite-facies lithologies are widespread in northern Mozambique, and Grt+Cpx-bearing assemblages show that high-P granulitefacies conditions with PT reaching 1.55 GPa and 900ºC were reached during the Pan-African orogeny. Garnet is replaced by symplectites of Pl+Opx+Mag indicating isothermal decompression, and the subsequent formation of Pl+amphibole-coronas suggests cooling into amphibolite facies. It is concluded that high-T metamorphism was pervasive in EAAO in Late Neoproterozoic/Early Paleozoic time, strongly overprinting evidences of earlier metamorphic assemblages.
Keywords: Dronning Maud Land; geologi

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi